2021
DOI: 10.1097/md.0000000000026464
|View full text |Cite
|
Sign up to set email alerts
|

Stroop interference in children with developmental dyslexia

Abstract: Previous studies have identified inhibitory deficits in dyslexic children, but we have little understanding of their neural mechanisms, especially for Chinese children with developmental dyslexia. We used a double-blind controlled trial to study the electroencephalogram responses of dyslexic and non-dyslexic children when performing the Stroop color-word test. Behavioral data showed differences in response time and accuracy between the 2 groups. In the event-related potentials (ERP) resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…In contrast, if access to the lexicon of mismatching words is slow and is an inescapable step before color naming in poor readers, they will produce larger Stroop interference. The latter case has been supported by considerable evidence (Faccioli et al, 2008; Levinson et al, 2018; Protopapas et al, 2007; Shen et al, 2021; Wu et al, 2018; but see Samuels, 1999). In this case, poor performance in the Stroop task for DD individuals may be caused by struggling with either access to the lexicon or inhibition of the meaning of mismatching words, which can be distinguished by comparing the Stroop color-word and RAN tasks.…”
Section: The Use Of Eye Tracking Techniques and Rapid Automatic Namingmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, if access to the lexicon of mismatching words is slow and is an inescapable step before color naming in poor readers, they will produce larger Stroop interference. The latter case has been supported by considerable evidence (Faccioli et al, 2008; Levinson et al, 2018; Protopapas et al, 2007; Shen et al, 2021; Wu et al, 2018; but see Samuels, 1999). In this case, poor performance in the Stroop task for DD individuals may be caused by struggling with either access to the lexicon or inhibition of the meaning of mismatching words, which can be distinguished by comparing the Stroop color-word and RAN tasks.…”
Section: The Use Of Eye Tracking Techniques and Rapid Automatic Namingmentioning
confidence: 91%
“…Children with Chinese DD have deficits not only in phonological awareness but also orthographic awareness, working memory, and parafoveal processing (Cao et al, 2017; Pan et al, 2013; Wang et al, 2010). Studies using the Stroop color-word test have indicated larger Stroop inference in DD than in typically developing children (Levinson et al, 2018; Shen et al, 2021; Wu et al, 2018). These findings indicate that phonology processing deficits cannot independently explain the cognitive mechanisms underlying dyslexia.…”
Section: The Deficits Of Ddmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants will be asked to respond only when any word in a red font appears (Go trial). The Go trial consists of congruent (color and word match) and incongruent (color and word mismatch) conditions [ 43 ]. The ratio between congruent and incongruent groups is 1:1 [ 43 ], and the task consists of 10 trials each, for the Go and No-Go paradigms.…”
Section: Methodsmentioning
confidence: 99%
“…The Go trial consists of congruent (color and word match) and incongruent (color and word mismatch) conditions [ 43 ]. The ratio between congruent and incongruent groups is 1:1 [ 43 ], and the task consists of 10 trials each, for the Go and No-Go paradigms. In addition to the Go/No-Go task, the reaction time was prolonged compared to SRT in healthy volunteers ( n = 4; M = 38.5 years, SD = 12.2; Supplementary Figure S3A, Additional file 1 ).…”
Section: Methodsmentioning
confidence: 99%